The Impact of Education Management Systems on the Success of Implementing Islamic Curriculum in Indonesian Higher Education Institutions - H. Asep Idrus Alawi (International Journal of Educational Research, 2024)
Islamic education is equally important in a Muslim's life as any other level of education. To assess the successful inclusion of Islamic education in Indonesian higher education institutes, this study looked into the successful execution of the Islamic education curriculum via the education management system. The study used a qualitative research approach, with higher education institutes inside Indonesia's demographic boundaries being investigated and data collected. Semi-structured interviews were used to obtain data from higher authorities and administrative workers who interact with the Islamic curriculum in higher education establishments. The data was analysed using thematic analysis, which resulted in various themes indicating several potential constructs that defined the successful implementation of the Islamic education curriculum, such as systematic approaches, cultural alignment, structured decision making, agile response systems, and so on. The contributions, limits, and future ideas are discussed in the peripheral portions of the study.